2019
DOI: 10.1007/s40866-019-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renewable Energy to Achieve Energy Sustainability in Iran. An Economic and Technical Analysis of the Hybrid Power System

Abstract: The aim of this study is an economic and technical analysis of a hybrid system in the Semirom city of Iran that is performed by a technical-economic analysis on combined utilization of solar-wind and diesel system. In this study HOMER software is utilized for economic assessment and optimization. At first, the related meteorological data gathered and then using Homer software the calculation was carried out. This city has good potential for solar and wind energy. The solar radiation ranges of Semirom city is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In the past decade, a number of methods have been presented for the economic quantification of various mitigation techniques. For instance, in the paper [20], authors provided a technical and economic assessment of a hybrid system in the city of Semirom in Iran which was carried out by a technoeconomic assessment on combined utilization of diesel and solar-wind sub-system. Additionally, in recent years, wide variety mitigation methods have been provided at different levels of system hierarchy, to ensure appropriate PQ implementation at point of delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past decade, a number of methods have been presented for the economic quantification of various mitigation techniques. For instance, in the paper [20], authors provided a technical and economic assessment of a hybrid system in the city of Semirom in Iran which was carried out by a technoeconomic assessment on combined utilization of diesel and solar-wind sub-system. Additionally, in recent years, wide variety mitigation methods have been provided at different levels of system hierarchy, to ensure appropriate PQ implementation at point of delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adefarati et al [14] have presented the benefits of using renewable energy sources for reliability, environment and economics parameters like cost of energy, life cycle cost, the annual cost of load loss and life cycle greenhouse gas emission cost. Razmjoo et al [15] have performed technoeconomical analysis for combined utilization of solar, wind and diesel energy for supplying selected load of Semirom city of Iran and presented economic viability of renewable energy use. Kumar et al [16] have designed a hybrid standalone Wind-PV-Battery system to supply electricity for technical university campus located in north-west Indian state Rajasthan and found that optimal generation unit price is compatible with grid extension case.…”
Section: Introductionmentioning
confidence: 99%
“…The techno-economic analysis for grid-connected and off-grid systems at different cities at the Arabian Peninsula and KSA using a combination of HRES such as PV, wind turbine, fuel-cells, and battery were provided in [15][16][17][18][19][20][21][22]. The authors in [15] reviewed the recent control strategies for energy management in hybrid renewable energy system.…”
Section: Introductionmentioning
confidence: 99%
“…The paper concluded that the PV/diesel/battery hybrid configuration is found as optimum configuration with better performance in fuel consumption and a reduction in CO 2 emissions. Another study in [18] implemented economic and technical analysis of solar-wind and diesel system. The study concludes that the optimum hybrid system could generated a required energy and reduce greenhouse emission by integrating 15 kW PV array, 2 wind turbines, 1 kW diesel generator, 13,603 kW of battery, and 1 kW converter.…”
Section: Introductionmentioning
confidence: 99%